MODIFIKASI MODEL BOUSSINESQ DENGAN MEMANFAATKAN MODEL OPTIMASI - Mayandel Valerio, Richie
Tsunami has caused tremendous loss to human society. As it often comes suddenly, we need to fortify our mitigation strategies against this catastrophe. One way to do this is by deepening our knowledge regarding tsunamis and its characteristics. In this research, we will be investigating four sea floor movements that could cause tsunamis. We use the Boussinesq equations to examine the generated tsunami waves and simulate them numerically using the finite volume method. Then, we will employ the genetic algorithm as a strategy to improve the solution obtained previously. We shall witness that this model and method have produced desirable results, and their quality has also improved using the previously mentioned optimization method. We hope this research could contribute to the further understanding of tsunami knowledge and provide prominent information to develop warning systems or other mitigation strategies.